Colored and semitransparent silver nanoparticle layers deposited by spin coating of silver nanoink. (5th April 2018) - Yoon, Hoi Jin; Jo, Yejin; Jeong, Sunho; Lim, Jung Wook; Lee, Seung-Yun
Abstract: In this letter, we report on the fabrication and characterization of colored and semitransparent silver nanoparticle layers. A spin coating of silver nanoink is used to deposit silver nanoparticle layers onto substrates. The transmittance and color of the silver nanoparticle layers are significantly dependent on the spin speed and nanoink concentration, owing to variations in the size and distribution of the nanoparticles. Both color variation and efficiency improvement are achieved with the application of silver nanoparticles to semitransparent Si thin-film solar cells, which is associated with the excitation of the dipole or quadruple plasmon modes of the silver nanoparticles.